Responses of rumen microorganisms and metabolites to different roughage of domesticated Tibetan sheep - Ren, Yue; Zhaxi, Yangzhong; Ciwang, Renzeng; Wang, Zhengwen; Liu, Mengjun (Frontiers in Microbiology, 2023)
Tibetan sheep can utilize high fiber feeds well. However, the mechanisms of rumen microbiota and metabolites in response to different roughage in a housed environment are still unclear. We fed Tibetan sheep with three different roughage diets: 50% whole corn silage (TS), 50% wheatgrass group (TW), and 25% each of whole corn silage and wheatgrass (TM). Subsequently, meat traits, rumen contents 16S rRNA and metabolomics were studied. The results showed that feeding wheat straw to Tibetan sheep significantly increased the abundance of bacteria such as Ruminococcus and Succiniclasticum in the rumen. These microorganisms significantly increased metabolites such as beta-alanyl-L-lysine, butanoic acid and prostaglandin E2. Eventually, production performance, such as carcass weight and intramuscular fat and meat quality characteristics, such as color and tenderness were improved by altering the rumen’s amino acid, lipid and carbohydrate metabolism. This study demonstrated that including 25% wheatgrass and 25% whole corn silage in the diet improved the performance of Tibetan sheep, revealing the effect of the diet on the performance of Tibetan sheep through rumen microorganisms and metabolites.